The Effect of the Blended Learning Model on Social Attitudes and Improvement of Cognitive Learning Outcomes of Science Grade VII Students - Shelly Efrihani; Saipul Annur; Diki Diki (Universitas Muhammadiyah Enrekang, 2024)
The blended learning model is a combination of learning strategies that are implemented by presenting a variety of learning resources for students to help expand and deepen individual learning understanding of a learning material. Therefore, this study aims to find out and describe the influence of the blended learning model on social attitudes, students' cognitive learning outcomes, and the improvement of cognitive learning outcomes of science after the application of the blended learning model. In addition, this study also aims to find out and describe the influence of the blended learning model on the cognitive learning outcomes of science students in grade VII through social attitudes. In the collection of research data, the research method used in the implementation of this research is a quasi-experimental method (quasy experiment) with a research design, namely one group pretest-postest design. The research sample used was students in grade VII A SMP Negeri 2 Martapura OKU-Timur with a total of 30 students as an experimental class. In the research data collection procedure, the data collection methods used include using questionnaires/questionnaires and test methods. In the data testing stage, the application of the blended learning model had a significant influence on both students' social attitudes and students' cognitive learning outcomes in science with a calculated significance result of 0.00 < 0.05. Meanwhile, in the third test, the application of the blended learning model did not have a significant influence on students' cognitive learning outcomes in science through their students' social attitudes as shown by the t-count value obtained of 0.1049 < 2.052 (t-table). Then, in the fourth test, it was explained that there was an increase in the cognitive learning outcomes of science students in grade VII by using a blended learning learning model with an N-gain of 0.487 with the category of moderate/moderate improvement